PENGEMBANGAN E-LKPD BIOLOGI BERBASIS PROBLEM BASED LEARNING TERINTEGRASI STEM PADA MATERI SISTEM PEREDARAN DARAH KELAS XI SMA - Windi Riana Sari; Azza Nuzullah Putri; Erda Murhartati (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2022)
This study aims to produce an E-LKPD Biology Based on Problem Based Learning Integrated STEM on the Circulatory System Material that is valid, practical and effective for use in biology learning in class XI SMA. This research is a research and development (Research & Development) using a 4-D model. The instruments used were validation sheets of media experts and material experts, practicality sheets of teachers and students, an evaluation sheets posttest. The data obtained were analyzed descriptively quantitatively and qualitatively. The results of research and development of E-LKPD based on  Problem Based Learning Integrated STEM show that the average results of material validation and media validation are very valid categories. The results of the practicality test of teachers and students show a very practical category. For the results of the effectiveness of the results N-gain score obtained high category. Thus, it can be concluded that the E-Integrated BiologyLKPD is STEM valid, practical and effective for students of class XI SMA.